Proteomic analysis and genome annotation of Pichia pastoris, a recombinant protein expression host. Issue 23 (20th November 2014) - Renuse, Santosh; Madugundu, Anil K.; Kumar, Praveen; Nair, Bipin G.; Gowda, Harsha; Prasad, T. S. Keshava; Pandey, Akhilesh; Pandey, Akhilesh; Pevzner, Pavel A.
<x xml:space="preserve">Abstract</x> Pichia pastoris is a widely used eukaryotic host for production of recombinant proteins. We performed a proteogenomic analysis using high resolution Fourier transform MS to characterize the proteome of the GS115 strain. Our analysis resulted in identification of 46 889 unique peptides mapping to 3914 unique protein groups, which corresponds to ∼80% of the predicted genes. In addition, our proteogenomic analysis led to the discovery of 64 novel genes and correction of 11 predicted gene models. The strategy used here demonstrates the utility of high resolution MS‐derived peptide sequence data to cover near complete proteomes of organisms. Given the popularity of P. pastoris as a protein expression host, this proteome map should provide a list of contaminants derived from the host to assist in optimization of heterologous protein production. All MS data have been deposited in the ProteomeXchange with identifier PXD000627 (http://proteomecentral.proteomexchange.org/dataset/PXD000627).